Degradation-Based Burn-In Planning Under Competing Risks - Ye, Zhi-Sheng; Xie, Min; Tang, Loon-Ching; Shen, Yan (Technometrics, 2012)
Motivated by two real-life examples, this article develops a burn-in planning framework with competing risks. Existing approaches to planning burn-in tests are confined to a single failure mode based on the assumption that this failure mode is subject to infant mortality. Considering the prevalence of competing risks and the high reliability of modern products, our framework differentiates between normal and infant mortality failure modes and recommends degradation-based burn-in approaches. This framework is employed to guide the burn-in planning for an electronic device subject to both a degradation-threshold failure, which is an infant mortality mode and can be modeled by a gamma process with random effect, and a catastrophic mode, which is normal and can be represented with a conventional reliability model. Three degradation-based burn-in models are built and the optimal cutoff degradation levels are derived. Their validity is demonstrated by an electronic device example. We also propose three approaches to deal with uncertainty due to parameter estimation. Algorithmic details and proofs are provided in supplementary material online.